JAM AL-QUR’AN WA KITABATUHU: SEBUAH TINJAUAN SINGKAT PELUANG DAN TANTANGAN REFLEKSI MANA- JEMEN INFORMASI DAN ETIKA KEILMUAN DI ERA TEKNOLOGI - Ramlah Ramlah; Nasrullah Bin Sapa, Halimah Basri (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This article examines the collection and compilation of the Qur'an in the form of mushaf over the years, from the time of the Prophet Muhammad SAW to the time of Khulafaurrasyidin, especially during the time of the caliph Abu Bakar and the caliph Utsman Bin Affan. This process reflects the commitment of the Companions in maintaining the authenticity of the Qur'an text to be passed on to the next genera- tion. This research highlights the complexity and accuracy of the Qur'anic bookkeeping process and its relevance in the modern era. The background of this research focuses on understanding the history of the collection and compilation of the Qur'an as the holy book of Muslims. This study uses the literature re- view method, examining literature related to sources and views on the process of collecting and writing the Qur'an from the time of the Prophet Muhammad to the time of Khulafaur Rashidin. The results of the study show that the process of collecting and writing the Qur'an is a complex and structured effort carried out from the time of the Prophet Muhammad to the time of Khulafaur Rashidin This study also high-lights the relevance of the process of collecting and standardizing the Qur'an in modern information man- agement. This article suggests the importance of education on the history of Qur'anic bookkeeping, the use of technology for text conservation, the implementation of standardization in information manage- ment, as well as education on scientific ethics.